The effect of various drying methods on drying characteristics, sensory and nutritional qualities of yam - Kyere, Gladys (2016)
A thesis submitted to the Department of Food Science in partial fulfillment of the requirement for the award of the degree of Master of Science (Food Science and Technology), 2015